Global international relations and the Arab Spring: the Maghreb's challenge to the EU. Issue 10 (3rd October 2018) - Hill, J. N. C.
Abstract: This article contributes to the Global International Relations project by critically evaluating the roles ascribed to Europe and the EU by Levitsky and Way in their model for explaining regime transitions. Focusing primarily on their international dimensions of linkage and leverage, it assesses both the normative geopolitical underpinnings and explanatory power of their thesis, drawing on the North African cases of Tunisia and Mauritania at the start of the Arab Spring to illustrate and substantiate its observations and arguments. It concludes that the EU's failure to discipline either country's competitive authoritarian regime raises important questions about the validity of the privileged role in which they cast Europe.